Os sujeitos egressos prisionais: o retorno à liberdade e a (re) inserção social - Santos, Thalita Mara dos (2014)
This paper discusses issues about prison egresses and the process of social reinsertion of these individuals. Among the topics covered are discussions about the legal and institutional scenery of the prison egresses and reflections on the concept of the subject in the psychoanalytic context, as well as thoughts about the condition of the prison egresses and helplessness, according to Freud. The general objective of this paper consists in understanding the meaning of being an individual who is an egress of the prison system in the conception of the interviewed themselves. It is a qualitative research, in which depositions of seven collaborators, prison egresses, were considered, and the psychoanalytical method was used in the interpretation of the interviews. Considering the history of the people who passed through the prison system, that is, the pre-penal phase, the period of imprisonment, and the return to freedom, the meaning of being a prison egress pervades the need to deal with a concrete and objective reality hardly transformed, along with the aspects experienced during incarceration and all the subjective re-accommodations that the transition freedom-imprisonment-freedom imposes on the subjects, which encompasses the adaptation and misadaptation to the world inside and outside bars. The condition of the double helplessness of prison egresses leads to the fundamental helplessness along with the demands of dealing with the lack of guarantees of a better and more positive reality, as well as with expectations little optimistic and tied to a somber past of breaking up with a life of criminality.